FUNCTIONAL TRAINING OF WATER RESCUE GUARDS AND ENDURANCE IN THE COOPER TEST (Physical Culture and Sport: Scientific Perspective, 2024)
Annotation
Keywords: functional training; endurance; swimming endurance; the Cooper test; water rescue guards